2019
DOI: 10.3390/sym11020212
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of Software Defect Prediction: A Systematic Mapping

Abstract: Software defect prediction has been one of the key areas of exploration in the domain of software quality. In this paper, we perform a systematic mapping to analyze all the software defect prediction literature available from 1995 to 2018 using a multi-stage process. A total of 156 studies are selected in the first step, and the final mapping is conducted based on these studies. The ability of a model to learn from data that does not come from the same project or organization will help organizations that do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 154 publications
0
42
0
Order By: Relevance
“…The usage of machine learning algorithms has increased in the last decade and is still one of the most popular methods for defect prediction [51,52]. Challagulla et al [53] conducted an empirical assessment to evaluate the performance of various machine learning techniques and statistical models for predicting software quality.…”
Section: Related Workmentioning
confidence: 99%
“…The usage of machine learning algorithms has increased in the last decade and is still one of the most popular methods for defect prediction [51,52]. Challagulla et al [53] conducted an empirical assessment to evaluate the performance of various machine learning techniques and statistical models for predicting software quality.…”
Section: Related Workmentioning
confidence: 99%
“…They reported that CPDP achieved more successful results than WPDP and in WPDP polynomial kernel of SVM got better results while in CPDP linear kernel have achieved higher AUC.The AUC values were increased in all SVM functions when hyper-parameter optimization was applied. Son et al [35] conducted a systematic mapping in which he selected 98 studies out of 156 regarding defect prediction. They have reported that the most studied searchbased techniques used in defect prediction are the Artificial Immune Recognition System (AIRS), Ant Colony Optimization (ACO), Genetic Programming (GP), Evolutionary Programming (EP), Evolutionary Subgroup Discovery (ESD), GA, and Gene Expression Programming (GeP) and Particle Swarm Optimization (PSO).…”
Section: Related Workmentioning
confidence: 99%
“…One of the techniques that are used for optimization and prediction is called Genetics algorithm, and it is defined by Reference 15 as “a problem‐solving algorithm that uses genetics as a model of problem‐solving, also It's a search technique to find approximate solutions to optimization and search problems”. According to Son et al, 16 genetics algorithms have been studied once in the domain of fault prediction. Generally, genetics algorithms and genetic programming are rarely used in software engineering to predict faults, see for example References 17‐22.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that classification techniques are commonly used for defect prediction, 16 see Figure 1. Classification techniques for software fault prediction work to classify software modules into a faulty or non‐faulty module, and this type of prediction does not offer enough logistics to effectively distribute the required resources.…”
Section: Introductionmentioning
confidence: 99%